Routine deworming during antenatal care decreases risk of neonatal mortality and low birthweight: A retrospective cohort of survey data. - Bhavneet Walia; Brittany L Kmush; Sandra D Lane; Timothy Endy; Antonio Montresor; David A Larsen (Public Library of Science (PLoS), 2021)
Background Soil transmitted helminths (STH) are a common infection among pregnant women in areas with poor access to sanitation. Deworming medications are cheap and safe; however, the health benefit of deworming during pregnancy is not clear. Methods / principal findings We created a retrospective cohort of more than 800,000 births from 95 Demographic and Health Survey datasets to estimate the impact of deworming medicine during routine antenatal care (ANC) on neonatal mortality and low birthweight. We first matched births on the probability of receiving deworming during ANC. We then modeled the birth outcomes with the matched group as a random intercept to estimate the effect of deworming during antenatal care after accounting for various risk factors. We also tested for effect modification of soil transmitted helminth prevalence on the impact of deworming during ANC. Receipt of deworming medication during ANC was associated with a 14% reduction in the risk of neonatal mortality (95% confidence interval = 10-17%, n = 797,772 births), with no difference between high and low transmission countries. In low transmission countries, we found an 11% reduction in the odds of low birth weight (95% confidence interval = 8-13%) for women receiving deworming medicine, and in high transmission countries, we found a 2% reduction in the odds of low birthweight (95% confidence interval = 0-5%). Conclusions / significance These results suggest a substantial health benefit for deworming during ANC that may be even greater in countries with low STH transmission.